Immunotherapy and probiotic treatment for allergic rhinitis in children - Sumadiono Sumadiono; Cahya Dewi Satria; Nurul Mardhiah; Grace Iva Susanti (Paediatrica Indonesiana, 2018)
Background Allergic rhinitis is a global health problem that is increasing in prevalence. Many kinds of therapy have been tried, such as antihistamines, probiotics, and immunotherapy. Immunotherapy may restore the patient’s normal immunity against the specific allergen, while probiotics may modify the natural course of allergy. Objective To evaluate probiotics and immunotherapy for improving clinical symptoms of allergic rhinitis. Methods This randomized controlled trial (RCT) involved 64 patients, aged 3-18 years, and diagnosed with persistent allergic rhinitis in the Department of Child Health, Sardjito General Hospital from April 2016 until May 2017. Patients were randomly allocated into three therapy groups: group A (standard therapy/cetirizine only), group B (standard and probiotic therapy), and group C (standard therapy and immunotherapy). Clinical symptoms of allergic rhinitis including sneezing, rhinorrhea, and itchy nose, were evaluated for 7 weeks and classified as improved or not improved. The significance of the data was analyzed using proportion test. Results Sixty-four patients completed 7 weeks of therapy, 15 subjects in group A, 26 in group B, and 23 in group C. Group C showed significantly more improvement of sneezing and rhinorrhea compared to both group A (Z=5.71; Z=7.57, respectively) and group B (Z=2.82; Z=6.90, respectively). However, itchy nose was not significantly improved in group C compared to group B (Z=0.50), but was significantly improved in group C compared to group A (Z=10.91). Group B had significant improvement of sneezing, rhinorrhea, and itchy nose compared to group A (Z=3.81, Z=2.86, and Z=10.91, respectively). Conclusion The combined standard-immunotherapy group has significantly superior improvement compared to the combined standard-probiotic group and the standard therapy group, in terms of sneezing and rhinorrhea in children with persistent allergic rhinitis.